Diu Indo-Portuguese at present - Cardoso, Hugo C. (2006)
This note reports on the synchronic status and distribution of Diu Indo-Portuguese (henceforth DIP), while in the process presenting some preliminary linguistic data collected during a three-month period of fieldwork on the island in 2005.